Assessment of nitrite oxide and maternal–fetal Doppler parameters during pregnancy - Jorge Neto, Salim Demétrio; Machado, Jackeline Souza Rangel; Palei, Ana Carolina Tavares; Martins, Wellington Paula; Sandrim, Valéria Cristina [UNESP]; Araujo Júnior, Edward; Amaral, Lorena Machado; Tanus-Santos, José Eduardo; Duarte, Geraldo; Cavalli, Ricardo Carvalho (Taylor & Francis, 2016)
Objective: The objective was to evaluate and compare the whole blood nitrite concentration in the three trimesters of pregnancy. Additionally, we investigate whether there is any relation between nitrite concentrations and Doppler ultrasound analysis of some maternal and fetal vessels. Methods: Thirty-three healthy pregnant women were examined at the first (11–14 weeks), second (20–24 weeks) and third trimester (34–36 weeks) of pregnancy. In the three exams, we determined the maternal whole blood nitrite concentration and uterine arteries Doppler analysis to determine pulsatility index (PI), and resistance index (RI). In the second and third trimester we also performed fetal umbilical and middle cerebral arteries PI and RI. We compared the concentrations of nitrite in three trimesters and correlated with Doppler parameters. Results: No difference was observed in the whole blood nitrite concentrations across trimesters: 151.70 ± 77.90 nmol/ml, 142.10 ± 73.50 nmol/ml and 147.10 ± 87.30 nmol/ml; first, second and third trimesters, respectively. We found no difference in correlation between whole blood nitrite concentration and Doppler parameters from the evaluated vessels. Conclusions: In healthy pregnant women, the nitrite concentrations did not change across gestational trimesters and there was also no strong correlation with Doppler impedance indices from maternal uterine arteries and fetal umbilical and middle cerebral arteries.
Keywords: Doppler ultrasonography; nitrites; pregnancy